Analysis of the Future Distribution and Trend of Arctic Sea Ice Using CMIP6 Data - SHI Xudong; HE Tao; LI Min; LI Bingrui; LIU Simeng; XIE Lingling (Haiyang Kaifa yu guanli)
This study examines the future spatial distributions and long-term trends of the sea ice concentration (SIC) and the sea ice thickness (SIT) in the Arctic, along with the potential impacts of the Temperature at Surface (TAS), using the outputs of six models under four forcing scenarios of the Coupled Model Intercomparison Project Phase 6 (CMIP6). The results show that, under the four forcing scenarios, the SIC exceeds 50% and the SIT is approximately 1.5 m in most parts of the Arctic in 2030, 2040, and 2050. However, in the regions of East Greenland, the Barents Sea, the Kara Sea, and the Chukchi Sea, the SIC and SIT are comparatively lower and thinner. Both the SIC and the SIT exhibit declining trends during 2015—2050. Specifically, under the high-forcing scenario, the SIC in some regions decreases by over 1% per year. In 2050, under the high-forcing scenario, the SIC in most of the Arctic exceeds 90% during winter and spring months. The SIC reveals a decreasing trend in every month. The SIT exceeds 1 m from winter to summer in most regions, while it is less than or equal to 0.5 m in the fall. From December to May, the SIT exhibits a decreasing trend across the Arctic, with some localized increases observed in other months. Regarding the long-term trend up to 2100, the SIC and SIT in the Central Arctic, the East Greenland Sea, and the Chukchi Sea decrease over time, with the fastest reduction in the Central Arctic, meanwhile the TAS continues to rise in these three regions. Additionally, the spatial distribution and long-term trend between the TAS and the SIC are opposite, implying the possible impact of the TAS on the SIC. These findings provide valuable insights into the future sea ice in the Arctic under different forcing scenarios.